Optimalisasi Aplikasi Pengendalian Skripsi Menggunakan Algoritma Dynamic Priority Scheduling dan Sequential Search - Arief, Arya; Sari, Ratih Titi Komala; Mardiani, Eri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Thesis registration in the academic environment often faces priority and time management problems, therefore an effective and responsive approach is needed. This study suggests optimizing the Dynamic Priority Scheduling and Sequential Search algorithms to improve the performance of thesis control applications. Dynamic characteristics of students and service requests regulate submission priorities and a sequential search algorithm improves the search for thesis-related information in the database. This research discusses the ideas of both algorithms and how they can improve system efficiency by integrating them.